2018
DOI: 10.13052/jcsm2245-1439.634
|View full text |Cite
|
Sign up to set email alerts
|

Random Number Generators Basedon EEG Non-linear and ChaoticCharacteristics

Abstract: Current electroencephalogram (EEG)-based methods in security have been mainly used for person authentication and identification purposes only. The non-linear and chaotic characteristics of EEG signal have not been taken into account. In this paper, we propose a new method that explores the use of these EEG characteristics in generating random numbers. EEG signal and its wavebands are transformed into bit sequences that are used as random number sequences or as seeds for pseudo-random number generators. EEG sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In this system, the random cryptographic key generation includes the selection of features depending on normalized thresholds and the protocol of the segmentation window. Another EEG-based key generation system is proposed by Nguyen D et al 12 . This proposed system indicated that the EEG signal cannot be utilized directly as a source for generating random keys, rather it needs to be transformed before utilizing as random keys generator.…”
Section: Related Workmentioning
confidence: 99%
“…In this system, the random cryptographic key generation includes the selection of features depending on normalized thresholds and the protocol of the segmentation window. Another EEG-based key generation system is proposed by Nguyen D et al 12 . This proposed system indicated that the EEG signal cannot be utilized directly as a source for generating random keys, rather it needs to be transformed before utilizing as random keys generator.…”
Section: Related Workmentioning
confidence: 99%